2009
DOI: 10.1080/09084280802636371
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Attention in Children with Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) is a common cause of disability among children in the United States, and attention deficits are frequently observed in both the acute and chronic phases of injury. The current study investigated models of attention in children with TBI and examined differential sensitivity of various components of these attention models to the severity of the brain injury. Participants included 151 children and adolescents (mean age 12.9 years, SD=2.6) who had suffered TBI, and 50 normal controls (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
26
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 43 publications
5
26
1
Order By: Relevance
“…However, in the data presented by Ord and colleagues. there were some small to medium effect sizes noted between groups on Omissions T scores (d = .43) and raw scores {d = .45), Commissions raw score (d = .39), and Perseveration raw score (d = .47). Nonetheless, there was a lack of difference between TBI severity groups that was consistent with our own findings and with other recent studies comparing CPT-II performance between MTBI and moderate to severe TBI groups in adults (Kraus et al, 2007), and mild to moderate TBI and severe TBI groups in children (Park, Allen, Barney, Ringdahl, & Mayfield, 2009). Taken as a whole, these findings suggest that the sensitivity of the CPT-n to severity of TBI is questionable in both civilian and military populations.…”
Section: Discussionsupporting
confidence: 92%
“…However, in the data presented by Ord and colleagues. there were some small to medium effect sizes noted between groups on Omissions T scores (d = .43) and raw scores {d = .45), Commissions raw score (d = .39), and Perseveration raw score (d = .47). Nonetheless, there was a lack of difference between TBI severity groups that was consistent with our own findings and with other recent studies comparing CPT-II performance between MTBI and moderate to severe TBI groups in adults (Kraus et al, 2007), and mild to moderate TBI and severe TBI groups in children (Park, Allen, Barney, Ringdahl, & Mayfield, 2009). Taken as a whole, these findings suggest that the sensitivity of the CPT-n to severity of TBI is questionable in both civilian and military populations.…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with previous studies using different cognitive task-switching paradigms in TBI (Larson et al, 2006;Schroeter et al, 2007). These switching deficits in TBI patients may be related to attentional problems when transferring between different motor tasks (Park et al, 2009). In other words, patients with TBI have difficulty shifting attention in order to perform on-line modification of motor patterns during the execution of complex movements.…”
Section: Bimanual Coordination Deficits In Tbi Patientssupporting
confidence: 92%
“…Finally, the encode component allows for the brief retention of information that then is linked to various cognitive processes, including mental manipulation and recall, and may be associated with the hippocampal and amygdala function (Mirsky, 1987). Mirsky's model of attention has undergone considerable validation in children and adults, as well as in various clinical populations including schizophrenia (Allen et al, 1997;Combs & Gouvier, 2004), autism (Goldstein, Johnson, & Minshew, 2001), HIV encephalopathy (Levine et al, 2008), traumatic brain injury (TBI; Ewing-Cobbs, Prasad, & Fletcher, 1998;Park, Allen, Barney, Ringdahl, & Mayfield, 2009), and attention-deficit/hyperactivity disorder (ADHD; Mirsky et al, 1999). Factor analysis has confirmed the presence of the four attention components in many of these populations and demonstrated that the four components may be differentially affected in these disorders.…”
mentioning
confidence: 99%
“…However, Power and colleagues (Power, Catroppa, Coleman, Ditchfield, & Anderson, 2007) found that the amount of brain damage, rather than the location, predicted attentional deficits following pediatric TBI. Research on TBI populations using Mirsky's model has demonstrated that children with severe TBI performed poorer on the focus and shift components of attention than did children with mild and moderate TBI (Ewing-Cobbs et al, 1998) and that these two components further predicted TBI severity (Park et al, 2009). Additional research on the focus component suggests that this component is relatively spared in individuals with ADHD (Egeland, 2007;Marchetta, Hurks, De Sonneville, Krabbendam, & Jolles, 2008;Rodrigues, 2009).…”
mentioning
confidence: 99%